The Prognostic Impact of Radioiodine Therapy in Patients with Papillary Thyroid Cancer - Schott, Matthias; Schott-Ohly, Patricia; Krieg, Sarah; Thomaschky, Cora; Wieltsch, Jan-Hendrik; Petrovitch, Alexander; Krieg, Andreas (Hormone and Metabolic Research, 2024)
Radioiodine (RAI) therapy after surgery, is an important component for the treatment of patients with papillary thyroid cancer (PTC), the most common thyroid cancer. In this study we sought to evaluate the cancer-specific survival (CSS) impact of RAI in specific thyroid cancer subgroups. The Surveillance, Epidemiology, and End Results (SEER) database were used to identify patients with PTC who underwent surgery between 2000 and 2019. Patients not treated with RAI were compared to those treated with RAI using propensity score matching (PSM) on the basis of identical inclusion criteria. A total of 106 333 patients were identified from the SEER database. RAI therapy was associated with improved CSS in the matched cohort (HR: 0.83; 95% CI: 0.72–0.96, p=0.01) but not in the unmatched data set (HR: 1.46; 95% CI: 1.30–1.64, p<0.001) among all PTC patients regardless of disease stage. Detailed analyses, however, showed that only patients with high-risk disease (pT3N1, pT4N1) experienced the greatest benefit in CSS. In the lower disease stages, no significant differences were recognized in the group of PTC patients with or without RAI therapy. One exception: in the group of PTC patients in stage pT1bN0, a significant difference was seen towards RAI. This is, however, most likely due to the large number of patients investigated. In summary, RAI therapy should not be used in low-risk PTC patients and might be used to some extent in intermediate-risk PTC patients. The histological suptype of the tumor needs to be considered in this context.
Keywords: papillary thyroid cancer; radioiodine therapy; cancer-specific mortality; SEER database